2020
DOI: 10.1002/art.41420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Lactate Dehydrogenase A Activity and Aerobic Glycolysis on the Proinflammatory Profile of Autoimmune CD8+ T Cells in Rheumatoid Arthritis

Abstract: Objective CD8+ T cells contribute to rheumatoid arthritis (RA) by releasing proinflammatory and cytolytic mediators, even in a challenging hypoxic and nutrient‐poor microenvironment such as the synovial membrane. This study was undertaken to explore the mechanisms through which CD8+ T cells meet their metabolic demands in the blood and synovial membrane of patients with RA. Methods Purified blood CD8+ T cells from patients with RA, patients with psoriatic arthritis (PsA), and patients with spondyloarthritis (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 45 publications
4
77
0
Order By: Relevance
“…Peripheral blood CD8+ T cells from RA patients demonstrate enhanced glycolysis and lactate production compared with healthy controls or other types of inflammatory arthritis ( 46 ). This glycolytic phenotype was accompanied by decreased mitochondrial membrane potential and oxygen consumption in RA patient cells.…”
Section: Mitochondrial Metabolic Activity and Atp Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral blood CD8+ T cells from RA patients demonstrate enhanced glycolysis and lactate production compared with healthy controls or other types of inflammatory arthritis ( 46 ). This glycolytic phenotype was accompanied by decreased mitochondrial membrane potential and oxygen consumption in RA patient cells.…”
Section: Mitochondrial Metabolic Activity and Atp Productionmentioning
confidence: 99%
“…A glycolytic gene expression signature was also evident in CD8+ T cells from the RA synovium, which are predominantly present in ectopic lymphoid follicles. The reduced dependence on oxidative metabolism in the RA patient cells is thought to underlie their enhanced ability to proliferate in hypoxic conditions, and the RA T cells were shown to increase uptake of glutamine and its conversion to lactate when subjected to low oxygen and glucose ( 46 ). The increased lactate production from RA CD8+ T cells indicates that these cells are not subject to the same glycolytic checkpoints as seen in RA CD4+ T cells, however both metabolic phenotypes are associated with increased production of inflammatory mediators and are linked to disease processes.…”
Section: Mitochondrial Metabolic Activity and Atp Productionmentioning
confidence: 99%
“…By increasing availability of substrate for acetylation and shifting the T cell epigenome, LDH promotes Th1 commitment and IFN-γ production ( 64 ). A recent study has identified LDHA high expression as a feature of all CD8 + T cell subsets in RA patients ( 65 ). Inhibition of LDHA with FX11 (LDHA inhibitor) led to reduction in lipogenesis, migration, and proliferation of CD8 + T cells, and lowered CD8 + T cell effector functions ( 65 ).…”
Section: Glucose Metabolism As An Arthritogenic Risk Factormentioning
confidence: 99%
“…A recent study has identified LDHA high expression as a feature of all CD8 + T cell subsets in RA patients ( 65 ). Inhibition of LDHA with FX11 (LDHA inhibitor) led to reduction in lipogenesis, migration, and proliferation of CD8 + T cells, and lowered CD8 + T cell effector functions ( 65 ). LDHA inhibition successfully abrogated the ability of RA CD8 + T cells to sway healthy B cells toward a pro-inflammatory phenotype.…”
Section: Glucose Metabolism As An Arthritogenic Risk Factormentioning
confidence: 99%
See 1 more Smart Citation